Soft mobility planning for university cities: the case of Pavia - De Lotto, Roberto; Greco, Alessandro; Moretti, Marsilia; Pietra, Caterina; Venco, Elisabetta Maria (TeMA - Journal of Land Use, Mobility and Environment, 2022)
University City concept means a specific urban structure characterized by the maximum expression of the relations system (social, environmental, economic) that can exist between university institution and administrative/political institution: in particular, the physical connections linked to the spatial location of university structures within the urban fabric. In Pavia, between Municipality and University the development of common mobility strategies has been practically developed since the seventies of the XX century by Giancarlo De Carlo plan. From this period on, the centrality of the city emerged as magnet for the first and second tiers of adjacent Municipalities. The need to implement forms of sustainable mobility aimed at improving the connections between university and city center, useful also to trigger deep urban regeneration processes, carried to experiment a collaborative planning process between university, Municipality and the main involved stakeholders. The main aim is to develop an overall strategy throughout the entire municipal territory and to define lines of actions (tactics) for the creation of a soft mobility network within the Pavia context as University City. The participatory process is implemented with the use of a Collaborative Planning tool based on Google functionalities. In the paper, authors describe the main elements of this project.